Greening the Byte: A Roadmap for Sustainable Computing in the Digital Age - ZHAR , Dounia; ZHAR , Najoua; MAHIR , Fatima Zahra (Revue Internationale des Sciences de Gestion, 2025)
The digital revolution has transformed our world, but its rapid advancement carries a hidden cost: a growing environmental footprint. This paper delves into the critical challenge of green computing, exploring how we can harness the power of technology to build a more sustainable future. Through a comprehensive analysis of existing policies and regulations, we examine the effectiveness of various approaches to incentivize green computing practices. Case studies from diverse sectors showcase the tangible benefits of implementing sustainable solutions, from energy-efficient data centers to eco-conscious coding practices. The paper then explores emerging trends and research areas with the potential to revolutionize green computing. From the promise of quantum computing for environmental optimization to the rise of bio-inspired hardware, the future holds exciting possibilities for a greener digital landscape. We conclude by emphasizing the urgency and importance of continued research and development in green computing. By embracing a collaborative approach, bridging the gap between technological advancements and real-world implementation, and fostering a culture of environmental consciousness, we can pave the way for a digital future that thrives in harmony with the planet.